Bottle feeding in a breastfeeding world: unravelling the determinants shaping infant feeding choices - Akram, Huzaifa; Verma, Mamta; Velmurugan, R.; Khatri, Anamika; Kumari, Pragati (International Journal of Contemporary Pediatrics, 2025)
While WHO and UNICEF recommend breastfeeding as a preferred method of nutrition for infants due to its numerous health benefits, bottle feeding continues to be a common practice due to various factors, including personal, social, and environmental influences. These influences make bottle feeding a more practical or convenient option for many mothers. This discussion delves into the multifaceted determinants behind this practice. The aim of this review is to deepen the understanding of the context in which feeding choices are made and highlight the need to create supportive environments that help parents make the best possible decisions for their children’s health and well-being.